The Pancasila Deliberation Model: A Framework for Fostering Democratic Citizenship in Civic Education - Rahman , Arief; Irayanti, Irma (IAIN Madura, 2025)
This article examines the application of the fourth principle of Pancasila—deliberation to reach consensus—in civic education in Indonesia, aiming to cultivate democratic values and student character. The research employs a qualitative approach through a case study design, utilizing semi-structured interviews, classroom observations, and document analysis at SMA Negeri 1 Lhokseumawe. Findings indicate that most students appreciate the deliberation-based learning methods, although challenges such as communication barriers and varying learning styles persist. The role of teachers is crucial in facilitating active participation and creating an inclusive learning environment. The implications of this research highlight the need for continuous adaptation of teaching strategies to address diverse student needs, thereby enhancing the effectiveness of civic education and fostering responsible, engaged citizens.